Food logging: an information literacy perspective. Issue 2 (20th March 2017) - Cox, Andrew Martin; McKinney, Pamela; Goodale, Paula
Abstract : Purpose: The purpose of this paper is to explore the meaning of information literacy (IL) in food logging, the activity of recording food intake and monitoring weight and other health conditions that may be affected by diet, using applications (apps) accessed through mobile devices and personal computers. Design/methodology/approach: Data were gathered from a small group of food logging app users through a focus group and interviews. Analysis was informed by practice theory and the growing interest in IL outside educational settings. Findings: Food logging revolves around the epistemic modality of information, but it is the user who creates information and it is not textual. Food logging is associated with a discourse of focussing on data and downplaying the corporeal information associated with eating and its effect on the body. Social information was an important source for choosing an app, but data were rarely shared with others. Food loggers are very concerned with data quality at the point of data entry. They have a strong sense of learning about healthy eating. They were not well informed about the data privacy and access issues. Practical implications: Food loggers need to be better informed about data risks around food logging. Originality/value: This is the first study of food logging from an IL perspective.